(untitled) (Journal of Forensic Medicine & Toxicology, 2021)
Background- The general public’s interest in hand sanitizers has soared after the covid-19 pandemic pestilence. This gave rise to the notion that the use of such hand sanitizers may hinder the visibility of developed fingerprints. Methodology- Based on this hypothesis, a hand sanitizer was tested to see how it affected the detection of fingerprints left behind after use. Fingerprint detection techniques used included: ninhydrin, silver nitrate, iodine fuming and cyanoacrylate method. Result and conclusion- When hand sanitized fingerprints were compared to non-hand sanitized fingerprints, the alcohol-based hand sanitizers improved the visibility of fingerprints developed with ninhydrin and iodine fuming, and marginally improved those developed with silver nitrate and cyanoacrylate method. To determine the longevity of improved developed quality, various parameters such as time since hand sanitizer application prior to fingerprint deposition was tested.